2019
DOI: 10.1158/0008-5472.can-18-2139
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Derived IL1β and TNFα Regulate Arginine Metabolism in Neuroblastoma

Abstract: Neuroblastoma is the most common childhood solid tumor, yet the prognosis for high-risk disease remains poor. We demonstrate here that arginase 2 (ARG2) drives neuroblastoma cell proliferation via regulation of arginine metabolism. Targeting arginine metabolism, either by blocking cationic amino acid transporter 1 (CAT-1)-dependent arginine uptake in vitro or therapeutic depletion of arginine by pegylated-recombinant arginase BCT-100, significantly delayed tumor development and prolonged murine survival. Tumor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 50 publications
2
48
0
Order By: Relevance
“…Environmental hypoxia is known to affect ARG2 expression (59), and thus the differential oxygen tensions between a hypoxic tumor and a highly vascularized psoriatic lesion might result in altered ARG2 induction between disease states. The inflammatory cytokine milieu present within the tissue microenvironment might also alter ARG2 expression in Tregs, as TNF, IL-1B, and LPS can induce ARG2 within other cell types (60,61). Determining which factors in psoriatic lesions and in melanoma tumors may influence ARG2 expression could provide targets for future therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental hypoxia is known to affect ARG2 expression (59), and thus the differential oxygen tensions between a hypoxic tumor and a highly vascularized psoriatic lesion might result in altered ARG2 induction between disease states. The inflammatory cytokine milieu present within the tissue microenvironment might also alter ARG2 expression in Tregs, as TNF, IL-1B, and LPS can induce ARG2 within other cell types (60,61). Determining which factors in psoriatic lesions and in melanoma tumors may influence ARG2 expression could provide targets for future therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that the presence of TAMs facilitated up-regulation of MYC protein expression through the signal transducer and activator of transcription 3 (STAT3) pathway in non-MYCN-amplified neuroblastoma tumor cells, suggesting this may at least partially explain the finding that TAMs are associated with poor survival in non-MYCN amplified tumors ( 67 ). In comparison, another study analyzing 23 neuroblastoma tumor samples found that stage IV neuroblastoma tumors had higher expression of M1 macrophage markers, IL1-β and TNF-α, while stage I tumors had higher expression of M2 macrophage associated markers IL4, IL10, and TGF-β with IL1-β and TNF-α expression being associated with poor outcomes ( 115 ). These differences may be due to sample size, different subtype of neuroblastoma as the former study only included non-MYCN amplified tumors, or the locations of the biopsy samples as tumor microenvironments are often heterogeneous.…”
Section: Tams In Neuroblastomamentioning
confidence: 99%
“…TAM-derived enzymes arginase 1 and indoleamine dioxygenase 1/2 (IDO 1/2) catalyze metabolism of L-arginine and L-tryptophan respectively, and leads to suppression of effector T cell activation ( 110 ). A recent study showed that macrophage-derived IL-1 and TNF-α regulated arginine metabolism in neuroblastoma cells through a signaling pathway dependent on RAC-alpha serine/threonine-protein kinase (AKT) ( 115 ). Furthermore, in vitro studies suggest that neuroblastoma tumor cells can also promote M1 polarization of TAMs, leading to immune-metabolic cross-talk and a feedback loop that promotes neuroblastoma progression through tumor growth and immunosuppression ( 115 ); however, these findings have not yet been explored in vivo .…”
Section: Tams In Neuroblastomamentioning
confidence: 99%
“…The immune suppression-related genes including Socs3, Plaur (urokinase plasminogen activator receptor, uPAR), and Arginase 2 (Arg2) were significant decreased in the cluster in the volcano plot ( Fig. 8c), supporting that the immunosuppressive activities of macrophages were reduced in the KO mice 23,24,25 . In the other four clusters, three of them such as macrophage_Lars2, macrophage_Apoe, and macrophage_Dct were increased, and one of them,…”
Section: Macrophage and Dendritic Cell Clusters In Tils Support The Ementioning
confidence: 71%